Sh Paramjit Singh: A torch bearer of entrepreneurship in agricultural custom hiring - Jaidka, Manpreet; Brar, Amandeep Singh; Kaur, Ramanjit (Indian Farming, 2023)
Farmers having less than 2 hectares (5.0 acres) of farm land are referred as small and marginal farmers. They comprise about 86.2% of the country’s total farmers. In the era of intensive and mechanized crop production systems, timely and cost effective availability of agricultural implements to the small and marginal farmers plays a pivotal role in their decision making process. Due to small land holding and high market price of implements, small and marginal farmers cannot purchase all the machinery. So, establishment of custom hiring centers/machinery banks in the villages is need of the hour. Custom Hiring Centre (CHC) are basically a unit comprising a set of farm machinery, implements and equipment meant for custom hiring by farmers. The main objective of Custom Hiring Centre is to supply farm implements to small, marginal and poor farmers at subsidized rates on hire.